Meningoencephalitis tuberculosis as a paradoxical response to anti-tuberculous therapy in a child with pulmonary tuberculosis - a case report - Heda Melinda Nataprawira (Indonesian Pediatric Society, 2008)
This paper reports a case of meningoencephalitistuberculosis as a paradoxical response to anti-tubercu-lous therapy in a child with pulmonary tuberculosis.